2009
DOI: 10.1021/ie801004z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Methane Gas Production from Methane Hydrate

Abstract: A 72 L large-scale reactor vessel was designed, manufactured, and built to investigate the gas production from methane gas hydrates. Methane hydrates were successfully formed within the reactor using pure methane gas and deionized water in a sand matrix with grain sizes between 100 and 500 μm. Hydrate formation tests resulted in formation at 2.2 °C around 600 psi. Mass balance calculations show that 11% of the pore space volume was occupied by hydrate. Measurements and simulations suggest that hydrate was init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 22 publications
6
56
0
1
Order By: Relevance
“…During depressurization to 2.3 MPa, a stage of which the temperature of hydrate sample falls below freezing point was identified, and gas recovery was observed to increase during that stage. The increased gas recovery at low temperature was consistent with previous theoretical [136] and experimental studies [137], which is explained by a simultaneous dissociation of hydrate into water, ice and gas.…”
Section: Laboratory Experimentssupporting
confidence: 91%
“…During depressurization to 2.3 MPa, a stage of which the temperature of hydrate sample falls below freezing point was identified, and gas recovery was observed to increase during that stage. The increased gas recovery at low temperature was consistent with previous theoretical [136] and experimental studies [137], which is explained by a simultaneous dissociation of hydrate into water, ice and gas.…”
Section: Laboratory Experimentssupporting
confidence: 91%
“…Both concluded that the success of gas production was strongly dependent on the effective permeability and initial temperature of sediments. However, little work has analyzed the effects of natural gas hydrate reformation and ice generation on gas production, phenomena that are commonly observed when employing depressurization [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [26] carried out the hydrate dissociation experiment at a constant wellbore pressure of 1.0 MPa in a middle-sized cylindrical reactor, and found that the hydrate dissociation and gas production rates were both affected by the formed ice below the freezing point. Zhou et al [27] observed a cooling effect during methane hydrate dissociation via depressurization experiments in a 72 L large-scale reactor vessel. The temperature was found to jump to 0°C in an extremely short period because of ice formation.…”
Section: Introductionmentioning
confidence: 99%